IMPLEMENTASI PENDIDIKAN KARAKTER TANGGUNG JAWAB PESERTA DIDIK DI SEKOLAH MENENGAH ATAS - Muhammad Farhan Ramadhan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to determine the implementation process of responsible character education in SMA Negeri 43 Jakarta. The research method used in this study is a qualitative approach using descriptive methods. The data collection technique used is by means of observation, interviews, and documentation studies. The research subjects in this study included the principal and deputy principal, teachers, extracurricular coaches, and students. The data analysis technique used is the Milles and Huberman method which consists of data reduction by triangulation, data presentation, and drawing conclusions. The results of this study indicate that the process of implementing responsibility character education has been carried out by schools both in learning activities, in extracurricular activities, and carried out in habituation activities.